2019
DOI: 10.1001/jamapsychiatry.2019.0864
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia Reduction and the Association Between Left Ventral Striatal Reward Response and 6-Month Improvement in Life Satisfaction Among Young Adults

Abstract: IMPORTANCE Anhedonia is a symptom of multiple psychiatric conditions in young adults that is associated with poorer mental health and psychosocial function and abnormal ventral striatum reward processing. Aberrant function of neural reward circuitry is well documented in anhedonia and other psychiatric disorders. Longitudinal studies to identify potential biomarkers associated with a reduction in anhedonia are necessary for the development of novel treatment targets. OBJECTIVE To identify neural reward-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 67 publications
4
17
0
Order By: Relevance
“…We conducted repeated-measures ANCOVAs with the between-subjects factor group (HV, PTSD, MDD, SSD) and the within-subject factors emotion (happy, neutral, angry, fearful) and initial fixation (mouth, eyes) as well as the CTQ total score as continuous predictor. Medication indices were calculated following Eckstrand et al (2019) and entered as an additional covariate to investigate potential influences.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted repeated-measures ANCOVAs with the between-subjects factor group (HV, PTSD, MDD, SSD) and the within-subject factors emotion (happy, neutral, angry, fearful) and initial fixation (mouth, eyes) as well as the CTQ total score as continuous predictor. Medication indices were calculated following Eckstrand et al (2019) and entered as an additional covariate to investigate potential influences.…”
Section: Discussionmentioning
confidence: 99%
“…This cascade of events may occur in the long term (e.g., 9-23 years) [24,25], plausibly via higher levels of markers of inflammatory activity (e.g., peripheral cytokines) and chronic stress (e.g., cortisol) in the bloodstream [23,98]. The continuing effect of decreased LS on allostatic load may alter cardiorespiratory and neurophysiological pathways in the amygdala and left precuneus, ventromedial prefrontal cortex, and striatum brain regions over long durations [99,100]. Importantly, these areas have been identified as essential for executive functioning, optimal reward processing, and emotion modulation [101].…”
Section: Discussionmentioning
confidence: 99%
“…Although affective images have been used effectively to study anhedonia in specific populations [ 26 , 36 , 37 ], one consideration is whether these results generalize to a transdiagnostic sample as facial expressions are likely less intrinsically rewarding or pleasurable than actual rewards. Thus, reward processing paradigms might be more relevant to study neural mechanisms of anhedonia, and have been used effectively in transdiagnostic samples [ 40 ]. One neural activity measure, left vlPFC activity facial anger, was inversely related to baseline mania/hypomania.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies identified neural marker predictors of future affective symptoms in adolescents [ 38 , 39 ] and future changes in anhedonia in young adults [ 40 ]. Yet, to our knowledge, no studies attempted to identify neural marker predictors of future impulsivity.…”
Section: Introductionmentioning
confidence: 99%